2021
DOI: 10.1155/2021/5407664
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis on the Improvement of Symptoms and Prognosis of Gastrointestinal Tumors Based on Medical Care and Exercise Intervention

Abstract: Gastric cancer is a malignant tumor that originates from the epithelium of the gastric mucosa. It is the result of a combination of multiple factors, but the current research has not yet clarified its pathogenesis, so further research and exploration are needed. This article is mainly based on the meta-analysis of the improvement of gastrointestinal tumor-related symptoms and prognosis based on medical care and exercise intervention. The control group followed routine care after enrollment. In addition to rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although the prognosis of many GI cancers has improved over the past decades [ 2 , 3 ], a late cancer diagnosis is still the leading reason for cancer-related deaths among all GI cancers [ 4 ]. Current research focuses therefore on improving early cancer diagnosis, possibly leading to better outcomes among all GI cancers [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the prognosis of many GI cancers has improved over the past decades [ 2 , 3 ], a late cancer diagnosis is still the leading reason for cancer-related deaths among all GI cancers [ 4 ]. Current research focuses therefore on improving early cancer diagnosis, possibly leading to better outcomes among all GI cancers [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%